2011
DOI: 10.1063/1.3548831
|View full text |Cite
|
Sign up to set email alerts
|

The effects of size and orientation on magnetic properties and exchange bias in Co3O4 mesoporous nanowires

Abstract: Co 3 O 4 mesoporous nanowires with average single crystalline grain sizes of about 8 nm, 12nm, 25 nm, and 45 nm were synthesized by sintering of microwave-assisted hydrothermal processed belt-Co(OH) 2 precursors at 300-500 C for 2 h. Microstructure analysis was conducted by x-ray diffraction, x-ray photoelectron spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM), field emission SEM (FESEM), transmission electron microscopy (TEM), and high resolution TEM (HRTEM) to confirm the composition, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Moreover, many metal oxides show lattice expansion with a reduction of particle size which could be either because of the finite size effect, cation/anion vacancies, lattice stress etc . However, in general, Co 3 O 4 nanoparticles synthesized by using different methods exhibit the common trend of lattice expansion with an increase of particle size 3335 . For charge neutrality, some of the Co 3+ vacancies could be substituted by Co 2+ ions, which resulted in the contraction of the Co 2+ –O 2− bond length.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many metal oxides show lattice expansion with a reduction of particle size which could be either because of the finite size effect, cation/anion vacancies, lattice stress etc . However, in general, Co 3 O 4 nanoparticles synthesized by using different methods exhibit the common trend of lattice expansion with an increase of particle size 3335 . For charge neutrality, some of the Co 3+ vacancies could be substituted by Co 2+ ions, which resulted in the contraction of the Co 2+ –O 2− bond length.…”
Section: Resultsmentioning
confidence: 99%
“…Zeng et al . 35 reported the observation of a CEB field of −600 Oe from 25 nm Co 3 O 4 nanoparticles using a cooling field of 50 kOe arising from the intercoupling between a spin-glass-like shell and an uncompensated AFM core. Wang et al .…”
Section: Resultsmentioning
confidence: 99%
“…Zeng et al found the size and orientation dependence of the room-temperature ferromagnetic performance of antiferromagnetic Co 3 O 4 nanowires. 26 Karthik et al demonstrated the possible asperomagnetism and/or spin glass behavior of the NiO nanoparticles with a size of 16 nm. 9 The ferromagnetic Fe 3 O 4 nanoparticles show superparamagnetic properties when the particle size is less than ∼30 nm.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Bulk Co 3 O 4 has a spinel structure with Co 3+ ions occupying the B sites (octahedral) and the Co 2+ ions occupying the A sites (tetrahedral) and is antiferromagnetic (AFM) below 40 K, whereas it is paramagnetic (PM) above that temperature. , However, the magnetic measurements of mesoprous Co 3 O 4 samples show that the magnetic behaviors are mainly effected by the uncompensated surface spins. Mesoporous Co 3 O 4 samples were prepared using SBA-15, ,, KIT-6, ,,,, and SBA-16 , as hard silica templates and have been studied using magnetometry. In these studies, different types of mesoporous silicas were used as a hard template for the syntheses: the Co 3 O 4 replica of SBA-15 consists of nanowires with an average diameter of about 8 nm and the nanowires surface disorder the exchanges bias field changes systematically .…”
Section: Introductionmentioning
confidence: 99%